2021
DOI: 10.1177/20552076211033424
|View full text |Cite
|
Sign up to set email alerts
|

Participant views and experiences of sexual health research: The Contraception Choices online trial

Abstract: Background Online sexual health research can be convenient, efficient and low cost, but there are debates about the adequacy of online informed consent, privacy, and the acceptability of different methods of follow-up. Objectives To explore women's views and experiences of the Contraception Choices feasibility trial procedures and the place of digital interventions for contraception decision making. Methods We analysed data from two sources: (1) Qualitative interviews. Eighteen interviews were conducted with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Online platforms are attractive to users because of their convenience, diversity of information, and anonymity (Wu & Zhang, 2022). While information about contraception is widely available online, the quality is variable and the content can be misleading (Bailey et al, 2021). Lindley et al (2012) reported that limited online sexual health resources are available to lesbians.…”
Section: Lack Of Knowledgementioning
confidence: 99%
See 4 more Smart Citations
“…Online platforms are attractive to users because of their convenience, diversity of information, and anonymity (Wu & Zhang, 2022). While information about contraception is widely available online, the quality is variable and the content can be misleading (Bailey et al, 2021). Lindley et al (2012) reported that limited online sexual health resources are available to lesbians.…”
Section: Lack Of Knowledgementioning
confidence: 99%
“…The website provides information and support to make informed choices about contraception. The site aims to address the advantages and disadvantages of twelve contraceptive methods and to take women's preferences into account (Bailey et al, 2021). Bailey et al (2021) reported that women who had used the Contraception Choices website found it engaging, convenient and helpful.…”
Section: Lack Of Knowledgementioning
confidence: 99%
See 3 more Smart Citations